Effects of Prolonged High Phosphorus Diet on Phosphorus and Calcium Balance in Rats - Tani, Yoshiko (the Society for Free Radical Research Japan, 2007)
The amount of phosphorus contained in food as food additives is currently increasing and a high intake of phosphorus can cause various diseases. To determine the effects of a prolonged high phosphorus diet, here we investigated the phosphorus and calcium balance and expression of type IIa sodium-dependent phosphate transporter (Npt IIa) in mature rats. Wistar male rats (8-weeks old) were divided into five groups and fed diets containing 0.6% calcium plus 0.3, 0.6, 0.9, 1.2 or 1.5% phosphorus for 4 weeks. Urinary and fecal phosphorus excretions were significantly increased by the high phosphorus diets (from 0.6 to 1.5%), dependent on the amount of dietary phosphorus. The net absorption of intestinal phosphorus was also significantly increased by high phosphorus diets. As a result, a negative phosphorus balance was observed in rats given the 1.2% or 1.5% phosphorus diets. Serum parathyroid hormone and 1,25-dihydroxyvitamin D(3) concentrations were increased by high phosphorus diets. In addition, high phosphorus diets decreased the expression of Npt IIa mRNA and protein in the renal brush border membrane. Taken together, these results suggest that diets containing 1.2 or 1.5% phosphorus plus 0.6% calcium have potentially adverse effects on phosphorus homeostasis in mature rat.